Development of free cooling based ventilation technology for buildings: Thermal energy storage (TES) unit, performance enhancement techniques and design considerations – A review. (May 2016) - Alizadeh, M.; Sadrameli, S.M.
Abstract: Nowadays, one of the major challenges for administrations and governments is energy demand to satisfy thermal comfort in the buildings. In energy systems where a temporal difference exists between the supply of energy and its utilization, thermal energy storage is necessary to ensure the continuity of a thermal process. The development of thermal energy storage systems has been under consideration for a variety of applications such as solar thermal energy storage, waste heat recovery, free cooling, etc. Free cooling night ventilation is the process of storing the coolness in the night time and releasing this coolness in hot day time. Free cooling has attracted considerable attention in the last few years. Supreme efforts have been put into finding new powerful free cooling systems and quantifying their economic and technical feasibility for thermal comfort in buildings. This paper presents a review of studies focused on the free cooling application in the residential and commercial buildings. Many considerations have been highlighted in this review including the merits, demerits and limitations of the free cooling systems for buildings application. The application of phase change materials (PCMs) in the free cooling, thermal enhancement techniques, technical, geographical and economical aspects and their performance evaluation criteria have also been reviewed. A few studies that reported in the literature for the numerical modeling of PCMs have also been discussed and therefore this overview stresses the need to discuss numerical modeling of free cooling deeply.